Diagnostic traction and dorsal locking plate stabilization of a fifth and sixth thoracic vertebral fracture/luxation in a golden retriever: Case report - Tammaro, William J.; Early, Peter J.; Bergman, Robert; Petrovsky, Brian L.; Kraus, Karl H. (Frontiers in Veterinary Science, 2022)
Traction was used to diagnose instability of a T5-T6 traumatic luxation that was stabilized with locking plates in the laminae and dorsal pedicles. A two-year-old, 27kg, female spayed golden retriever presented to a veterinary teaching hospital after being referred for possible mandibular and spinal fractures after being hit by a car. The dog presented weakly ambulatory paraparetic with intact pain perception. Computed tomographic (CT) imaging showed a fifth and sixth thoracic vertebral fracture/luxation, with and without manual traction. Surgical stabilization of the spine was performed with bilateral dorsally placed locking plates (String-of-Pearls, Orthomed, UK) in the laminae and dorsal aspects of the vertebral pedicles. The dog recovered well, and neurologic status improved significantly overnight and continued to improve up until discharge, which was six days postoperatively. Upon recheck exam at eight weeks postoperatively, the dog appeared neurologically normal with no obvious surgical complications. This case demonstrates that diagnostic traction – the process of, during imaging, pulling on the dog's pelvis while the head is secured – demonstrated instability of the spine which was not readily apparent on initial CT imaging. Additionally, the dorsal locking plate stabilization is a viable fixation option that provided acceptable stabilization of the mid-thoracic vertebrae.